Comparative analysis on emergence of Islamic education in Malaysia and Bangladesh - Nor, M.R.M.; Yusof, A.; Atikujjaman, M.; Mohd Zin, M.Z.; Mahdi, A.F.; Sakat, A.A.; Adi Yasran, A.A.; Samasu, S.F. (AENSI, 2012)
This paper explores the evolution of Islamic educational arrangement between Malaysia and Bangladesh. It is mainly focused on background, silhouette and prospect prediction of Islamic education in both countries. The point on background explains the way of introduction to Islamic education system before gaining independence from Britain.. Post-independence consequence has also discussed as the second portion of this study. Final discussion focused on the present status of Islamic education in Malaysia and Bangladesh with a comparative analysis on the subject matter.